Case Report: From multimodality imaging to catheter ablation of ventricular arrhythmias in arrhythmogenic mitral valve prolapse - Alzammam, Ali; Alanazi, Faisal; Alenazy, Sultan; Alsalman, Abdulmahsen; Albadi, Abdulrahman; Almegbel, Maysan; Aljizeeri, Ahmed; Altaweel, Muneera; Almusaad, Abdulmohsen (Frontiers in Physiology, 2025)
BackgroundMitral valve prolapse (MVP) is a common condition, typically benign, but in a small subset of patients, it may lead to life-threatening arrhythmias and sudden cardiac death (SCD). This arrhythmogenic MVP phenotype is often associated with bileaflet prolapse, mitral annular disjunction (MAD), and myocardial fibrosis identified via late gadolinium enhancement (LGE) on cardiac MRI.Case SummaryOur patient is a 49-year-old man presented with monomorphic ventricular tachycardia and near-syncope. Echocardiography showed bileaflet MVP, MAD and mild mitral regurgitation. Cardiac MRI revealed fibrosis in the papillary muscle. Electrophysiological study (EPS) confirmed inducible ventricular fibrillation (VF) triggered by papillary muscle PVCs. Catheter ablation was successfully performed, eliminating the arrhythmic focus. Despite successful ablation, an implantable cardioverter-defibrillator (ICD) was implanted for secondary prevention, given the high-risk structural substrate. The patient remained arrhythmia-free over 2 years of follow-up.DiscussionThis case highlights critical diagnostic markers—bileaflet prolapse and LGE—associated with arrhythmogenic MVP. While ablation may suppress triggers, it does not completely eliminate the underlying substrate. Current expert consensus supports ICD implantation in patients with sustained VT/VF or sudden cardiac arrest, regardless of ablation success. Management should be individualized based on risk profile, imaging findings, and clinical presentation.ConclusionMalignant MVP warrants comprehensive evaluation with echocardiography, cardiac MRI, and EPS. Catheter ablation is effective in eliminating arrhythmic foci, but ICD therapy remains essential for secondary prevention. Future high-quality trials and clear guidelines for diagnosis, risk stratification, and management are essential to avoid both over- and under-treatment, ensuring optimal outcomes for the patients with MVP.